The Impact of Social Media on Reproductive Health Knowledge Among Gen Z - badrun, alia; Rikha Putri Nabila; Desy Hermayanti (Universitas STRADA Indonesia, 2024)
Social media plays a significant role in the lives of Generation Z, especially in influencing knowledge and behavior related to reproductive health. This study aims to describe the impact of social media on reproductive health among generation Z, including the issue of early marriage, risky sexual behavior, and pregnancy outside of marriage. The results showed that free access to pornographic content and lack of reproductive health education are the main factors that encourage these negative behaviors. Early marriage risks causing health complications such as LBW, anemia, and hypertension, while risky sexual behavior increases the rate of sexually transmitted infections (STIs). In addition, pregnancy outside of marriage often occurs due to low knowledge of reproductive health and weak parental supervision. Prevention efforts involve the active role of the government, parents, and proper education to build a good understanding of reproductive health. Thus, controlling the use of social media and increasing reproductive health literacy are important solutions to overcome this problem among Generation Z.